2019
DOI: 10.21203/rs.2.19409/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNAs as potential biomarkers for the diagnosis of traumatic brain injury: a systematic review and meta-analysis

Abstract: Background: Traumatic brain injury (TBI) is a sudden trauma on the head, commonly associated with death and long-term disability. MicroRNAs (miRNAs) are potential biomarkers of diverse diseases, including TBI. However, few systematic reviews and meta-analyses have been conducted to determine the clinical value of miRNAs expression in TBI patients.Methods: We did a comprehensive literature search to identify articles that have reported on the diagnostic and prognostic value of miRNAs expression in TBI patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…t-tau levels are elevated at various injury severities 174,203 , and in association with DAI 83,216 , as early as 1 hour after TBI and correlated with positive findings on CT 185,217 , as well as self-reported symptoms after mild TBI 66 . Micro RNA (miRNAs) are small molecules that contribute to gene expression regulation, blood, CSF and brain tissue levels 184,189,[218][219][220][221][222] . It has been demonstrated that miRNA expression is altered across all TBI severities over time periods ranging from 1 hour to several days posttrauma 184,223,224 .…”
Section: 1mentioning
confidence: 99%
“…t-tau levels are elevated at various injury severities 174,203 , and in association with DAI 83,216 , as early as 1 hour after TBI and correlated with positive findings on CT 185,217 , as well as self-reported symptoms after mild TBI 66 . Micro RNA (miRNAs) are small molecules that contribute to gene expression regulation, blood, CSF and brain tissue levels 184,189,[218][219][220][221][222] . It has been demonstrated that miRNA expression is altered across all TBI severities over time periods ranging from 1 hour to several days posttrauma 184,223,224 .…”
Section: 1mentioning
confidence: 99%